Evolution of scoliotic spinal deformity after anterior spinal fusion - Petrenko, Dmytro; Mezentsev, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
In spite of progress in the modern spinal surgery, development of pseudarthrosis after anterior spinal fusion is still unresolved problem. The purpose of this study is to asses spinal fusion process in idiopathic scoliosis patients after anterior spinal instrumentation. Methods: retrospective analyses of radiographs and computer tomograms have been peen performed in 15 idiopathic scoliosis patients after anterior corrective spinal fusion. It is founded that spinal fusion developed 3 month after the surgery and radiographic Cobb angle values were without changes during 2 years follow-up. Conclusion: key factors for pseudarthrosis prophylaxis after anterior spinal fusion are stable spinal fixation with implant and total discectomy resulting in favorable condition for interbody spinal fusion.